Your brain on food : how chemicals control your thoughts and feelings - Wenk, Gary Lee (Oxford University Press, 2015)
In Your Brain on Food, Dr. Gary Wenk expands his discussion of the effects of specific foods on the brain in a completely updated second edition. From investigations into the benefits and risks of supplements, to the action of gluten in the brain and marijuana's potential for pain relief, Dr. Wenk draws on the latest science to answer a range of fascinating questions such as: -Is your aluminum cookware hurting you? -Can tryptophan supplements improve your mood? -How do fruits and vegetables protect us from aging? -Why does eating chocolate make you feel so angry? -Does our brain want us to be.